2021
DOI: 10.1016/j.surge.2021.01.008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of COVID-19 pandemic on the care of fragility hip fracture patients in the United Kingdom. A case control study in a major trauma centre

Abstract: Introduction Coronavirus disease 2019 is a pandemic that forced a transformation in the services provided by the National Health Service in the United Kingdom. Fragility hip fractures account for over 65,000 cases per year in the elderly population. The study aims to assess the impact of the pandemic on fragility hip fractures. Methods A retrospective data gather was performed to identify fragility hip fractures from the 23 rd of March 2020 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Few studies reported a reduced trend of fractures compared to the pre pandemic period [ 63 , 64 ]. Patients who experienced hip fragility fractures in the 2020 pandemic had a greater mortality compared to the same period of the pre pandemic era [ 65 , 66 ]. The 30- and 90-day mortality in positive patients with fragility hip fractures was greater, as was the time span from injury to surgical treatment, and the hospitalisation [ 59 , 67 71 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies reported a reduced trend of fractures compared to the pre pandemic period [ 63 , 64 ]. Patients who experienced hip fragility fractures in the 2020 pandemic had a greater mortality compared to the same period of the pre pandemic era [ 65 , 66 ]. The 30- and 90-day mortality in positive patients with fragility hip fractures was greater, as was the time span from injury to surgical treatment, and the hospitalisation [ 59 , 67 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of pressure ulcers in patients following surgery for femoral fractures was 21%, a considerable increase when compared to the 10% of the pre pandemic era [ 88 ]. Overall, patients who experienced hip fragility fractures in the 2020 pandemic had a greater mortality compared to the same period of the pre-pandemic era [ 65 , 66 ]. COVID infection directly contributed to increase the 30- and 90-day mortality following fragility hip fractures, not explained by patient characteristics [ 67 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hip fractures have still been very common during this time[ 4 , 25 , 28 ]; however, the pandemic has increased the mortality and complication rate particularly amongst COVID-positive patients[ 5 , 8 , 11 , 16 , 38 ]. The importance of early treatment and proper rehabilitation was strongly emphasized in order to ensure prompt recovery[ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Orfanos et al [ 14 ] performed a retrospective study on geriatric patients aged 60 years and above who sustained hip fracture after a fall in the United Kingdom. Of the 199 patients, 102 were included from the COVID-19 pandemic period and was compared to 97 patients from the same period in 2019.…”
Section: Clinical Presentationsmentioning
confidence: 99%
“…The sudden increased demand on healthcare resources led to a skewed distribution of these services in favour of COVID 19 infections [13]. As a consequence of this redistribution, other health services were impacted [28]. Elective surgical services which was the thrust of our investigation was also affected by various advisories curtailing these procedures as well as the difficulty posed by the various lockdowns which attempted to mitigate the spread of the virus [9] [15].…”
Section: Discussionmentioning
confidence: 99%